Concretização do direito ao desenvolvimento por meio do Mecanismo do Desenvolvimento Limpo - Borella, Marcela Cristina (2010)
The development consists on an expansion of human capabilities with respect to increasing the security and life expectancy, education, a dignified life and free citizen. Currently, besides the assurance of economic, social and cultural development, we seek to further that it is environmentally sustainable. The provisions of the United Nations Framework Convention on Climate Change and the mechanisms under the Kyoto Protocol, in particular the Clean Development Mechanism, seeking to reduce emissions of greenhouse gases by industrialized countries and promote sustainable development of the developing countries. Measures under the Kyoto Protocol to mitigate the climatic effects caused by the emission of greenhouse gases, should not be considered an obstacle to development, instead, should be seen as a tool for sustainable development in developing countries